Restitching Identities in Rural Sri Lanka : Gender, Neoliberalism, and the Politics of Contentment - Hewamanne, Sandya (Contemporary ethnography., 2020)
Continuing her earlier work on women free-trade-zone factory workers in Sri Lanka, Sandya Hewamanne here explores the ways in which these women negotiate their social and economic lives once back in their villages and highlights the complex effects of globalization and transnational production on communities in the Global South.